State repression on the Islamic political opposition in Indonesia in the period of 2017-2021 - Hasbi Aswar; Gustrieni Putri (Communications in Humanities and Social Sciences, 2022)
Repressive approach is one of the state's responses to social movements taken to restrain or limit the action of a movement that always strives for a social change process in society. In this context, Hizb ut-Tahrir and the Islamic Defenders Front (Front Pembela Islam – FPI) are two Islamic groups that recently after 2016 have been active in pressuring the government on various political issues. The government responded to these two groups with repressive measures such as stigmatization, criminalization, and dissolving or banning the organization. This study aims to discuss the details of government policies in responding to both HTI and FPI in Indonesia using comparative analysis by collecting secondary data from the media, books, and journals relevant with this study. This study found that the Indonesian government has used various means to repress HTI and FPI, such as intimidation, stigmatization, and disbandment to the organizations.